Avaliação espectrofotométrica do manchamento de resinas odontológicas contendo nanopartículas - Gomes, Larissa Bezerra de Mesquita (2010)
Composite resins have been subjected to structural modifications aiming at improved optical and mechanical properties. The present study consisted in an in vitro evaluation of the staining behavior of two nanohybrid resins (NH1 and NH2), a nanoparticulated resin (NP) and a microhybrid resin (MH). Samples of these materials were prepared and immersed in commonly ingested drinks, i.e., coffee, red wine and acai berry for periods of time varying from 1 to 60 days. Cylindrical samples of each resin were shaped using a metallic die and polymerized during 30 s both on the bottom and top of its disk. All samples were polished and immersed in the staining solutions. After 24 hours, three samples of each resin immersed in each solution were removed and placed in a spectrofotome ter for analysis. To that end, the samples were previously diluted in HCl at 50%. Tukey tests were carried out in the statistical analysis of the results. The results revealed that there was a clear difference in the staining behavior of each material. The nanoparticulated resin did not show better color stability compared to the microhybrid resin. Moreover, all resins stained with time. The degree of staining decreased in the sequence nanoparticulated, microhybrid, nanohybrid MH2 and MH1. Wine was the most aggressive drink followed by coffee and acai berry. SEM and image analysis revealed significant porosity on the surface of MH resin and relatively large pores on a NP sample. The NH2 resin was characterized by homogeneous dispersion of particles and limited porosity. Finally, the NH1 resin depicted the lowest porosity level. The results revealed that staining is likely related to the concentration of inorganic pa rticles and surface porosity